2019
DOI: 10.1186/s12866-019-1475-x
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and antibacterial effects of newly created lactic acid bacteria associations depending on cultivation media and duration of cultivation

Abstract: Background The newly created associations of lactic acid bacteria (LAB) isolated from Armenian dairy products (yoghurt, sour cream and different varieties of cheese), as well as from the gastrointestinal tract of honeybees were screened according to their antifungal and antibacterial activity. Results LAB strains were mixed at equal proportions (1:1) according to mathematical planning of experiments. Antifungal and antibacterial effects of different combinations (associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…The antibacterial activities of different probiotic strains play an important role as bio-preservatives in a wide range of dairy foods [ 43 , 44 ]. In the present work, the antibacterial activity of the ABT synbiotic yoghurt was evaluated by a disc diffusion assay, which was expressed as the inhibition zone against pathogenic strains.…”
Section: Resultsmentioning
confidence: 99%
“…The antibacterial activities of different probiotic strains play an important role as bio-preservatives in a wide range of dairy foods [ 43 , 44 ]. In the present work, the antibacterial activity of the ABT synbiotic yoghurt was evaluated by a disc diffusion assay, which was expressed as the inhibition zone against pathogenic strains.…”
Section: Resultsmentioning
confidence: 99%
“…Representatives of the genera Penicillium, Aspergillus, Monilia, Mucor, Endomyces, Cladosporium, Fusarium and Rhizopus are the most common spoilage fungi of bakery products (Legan, 1993;Salas et al, 2018). Production of mycotoxins is considered as one of the major problems associated with mold growth and is regarded as a potential public health hazard (Legan, 1993;Matevosyan et al, 2019;Sadiq et al, 2019). Application of different food associated LAB presents one potential option for bio-preservatives: most LAB have GRAS status and their safety has been proven over time.…”
Section: Discussionmentioning
confidence: 99%
“…Application of different food associated LAB presents one potential option for bio-preservatives: most LAB have GRAS status and their safety has been proven over time. It has previously been reported that some LAB can be producers of a variety of antifungal metabolites, including organic acids (Sadiq et al, 2019;Stiles, 1996); wide range of different low molecular weight compounds (Niku-Paavola et al, 1999;Salas et al, 2018); different peptides and proteins (Magnusson & Schnürer, 2001;Okkers et al, 1999) with potential for controlling spoilage moulds.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective case study described the adjunctive role of HBOT in mucormycosis with diabetes (94% survival) [49] . Calcineurin inhibitors and probiotics are the other adjunctive therapy used in various studies that showed a synergistic role along with L-AMB [ 50 , 51 ].…”
Section: Methodsmentioning
confidence: 99%